Development and validation of a questionnaire to measure the severity of pain, functional limitations, and reduction of sports ability for german-speaking patients with osteochondral lesions of the ankle (OCLA-G) - Heinz Lohrer; Stephanie Wagner; Markus Wenning; Jan Kühle; Hagen Schmal; Albert Gollhofer (BMC Musculoskeletal Disorders, 2023)
Abstract Background There is no patient-reported functional scale specific for osteochondral lesion of the ankle (OCLA). Therefore, the objectives of this study were to develop a questionnaire that measures symptom severity, function, and sports capacity in patients with osteochondral lesions of the ankle and to determine the psychometric properties of the tool in German language (OCLA-G). Methods The OCLA-G questionnaire was developed according to the COSMIN guidelines. Scalable items were generated from a literature search, based on an evaluation of 71 own OCLA patients, and from expert opinions. Following a twofold item reduction the questionnaire underwent explorative data analysis and principal component analysis. Validity and reliability were analysed in four groups of participants (40 patients with OCLA, 40 patients with other foot and ankle injuries, 40 asymptomatic athletes serving as a population at risk, and 40 asymptomatic persons playing sports not at risk). The minimum age for participation in the study was set at 18 years. The mean age was 39.3 ± 15.1 years. Results The final OCLA-G questionnaire consists of eight and five questions to mirror activities of daily life (ADL) and sports, respectively. Excellent internal consistency (Cronbach’s α = 0.950 for the ADL subscore and 0.965 for the sport subscale, respectively) was found. Spearman’s rank correlation coefficients for test-retest reliability were 0.992 for the ADL subscore and 0.999 for the sport subscale (p < 0.001). The results of the exploratory and confirmatory factor analyses indicated that item difficulty was between 23.4 and 62.8. The Pearson correlation for the OCLA subscales ADL and sport was 0.853 (p < 0.001). Construct validity as tested against the SF-12 questionnaire subscales (Physical and Mental component scale) were r = -0.164 to -0.663 (p < 0.05). Statistically, there was no ADL and sport OCLA mean score difference between OCLA patients and patients with other foot and ankle injuries (p = 0.993 and 0.179, respectively), but both groups differed from the uninjured control groups (p < 0.001). There were no ceiling or floor effects. Conclusions The OCLA-G was successfully developed as the first patient reported and injury specific outcome scale to measure the impact of OCLA induced symptoms on activities of daily living and sport. This study provides evidence for the reliability and validity of the OCLA-G assessing patients with OCLA. Trial registration The registration trial number is DRKS00009401 on DRKS. ‘Retrospectively registered’. Date of registration: 10/12/2015.